2019
DOI: 10.5385/nm.2019.26.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Newborn Infants with Prenatally Diagnosed Congenital Pulmonary Airway Malformation: A Single-Center Experience

Abstract: Purpose: Congenital pulmonary airway malformation (CPAM)-a rare developmental anomaly-affects the lower respiratory tract in newborns. By comparing the reliability of diagnostic tools and identifying predictive factors for symptoms, we provide com prehensive clinical data for the proper management of CPAM. Methods: We reviewed the medical records of 66 patients with prenatally diagnosed CPAM delivered at Severance Children's Hospital between January 2005 and July 2017. Results: We enrolled 33 boys and 33 girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This may be due to the inclusion of more severe patients in the university hospital. Previous studies have reported that adult patients with symptoms mainly have lesions in the lower lobe [14] . However, in this study, out of 12 adult patients diagnosed, 3 patients showed symptoms, with 2 cases (67%) involving the upper lobe and 1 case (33%) involving the lower lobe.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This may be due to the inclusion of more severe patients in the university hospital. Previous studies have reported that adult patients with symptoms mainly have lesions in the lower lobe [14] . However, in this study, out of 12 adult patients diagnosed, 3 patients showed symptoms, with 2 cases (67%) involving the upper lobe and 1 case (33%) involving the lower lobe.…”
Section: Discussionmentioning
confidence: 98%
“…Some patients undergo antenatal interventions such as thoracentesis, thoracocentesis, thoracoamniocentesis, and amniocentesis because fetal death may occur due to hydrops fetalis, hydrothorax, or severe oligohydramnios, and there are studies showing early surgery within the first week of life in neonates who develop symptoms such as severe respiratory distress after birth [12] . However, early planned surgery is sometimes performed in the absence of clinical symptoms after birth, but the appropriate timing of surgery remains controversial [13,14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation